Defective RNA polymerase III is negatively regulated by the SUMO-Ubiquitin-Cdc48 pathway - Wang, Zheng; Wu, Catherine; Aslanian, Aaron; Yates, John R, III; Hunter, Tony (eLife, 2018)
Transcription by RNA polymerase III (Pol III) is an essential cellular process, and mutations in Pol III can cause neurodegenerative disease in humans. However, in contrast to Pol II transcription, which has been extensively studied, the knowledge of how Pol III is regulated is very limited. We report here that in budding yeast, Saccharomyces cerevisiae, Pol III is negatively regulated by the Small Ubiquitin-like MOdifier (SUMO), an essential post-translational modification pathway. Besides sumoylation, Pol III is also targeted by ubiquitylation and the Cdc48/p97 segregase; these three processes likely act in a sequential manner and eventually lead to proteasomal degradation of Pol III subunits, thereby repressing Pol III transcription. This study not only uncovered a regulatory mechanism for Pol III, but also suggests that the SUMO and ubiquitin modification pathways and the Cdc48/p97 segregase can be potential therapeutic targets for Pol III-related human diseases.
Keywords: SUMO; Ubiquitin; neurodegeneration; post-translational modification; quality control; transcription